PERLINDUNGAN HUKUM ANAK LUAR NIKAH DI INDONESIA - Ahmad Dedy Aryanto (Fakultas Syariah Institut Agama Islam Negeri Palu, 2016)
The events of the birth of a human child resulting from a relationship not based on valid marriage bond will have an impact on the position of the child, which is the science of civil law known as the illegitimate child or a child out of wedlock. Children born out of wedlock have a negative impact on children in the eyes of the law. Status of children born will be uncertain because there is no authentic evidence to corroborate her that she is the legitimate child of his parents, his position in the eyes of the law is also regarded as an illegitimate son. Consequently, the child only has a civil relationship with the mother and the mother's family, that is, the child has no legal relationship to the biological father. State Concern for protection against illegitimate children is necessary given that no one on this earth who wants ambiguities concerning himself or in other words, no one is willing to bear the status of a child outside marriage. Clarity status, position, and protection under the law of a young man plays an important meaning in the footsteps tread life, the child is the legitimate child and moreover illegitimate child